Fast determination of peroxymonosulfate by flow injection chemiluminescence using the Tb(III) ligand in micelle medium. (18th November 2019) - Tang, Man; Zhang, Bo‐Tao; Teng, Yanguo; Liu, Meilin; Zhang, Yang
Abstract: Based on the chemiluminescence (CL) phenomenon of peroxymonosulfate (PMS) and Tb(III) enhanced by its ligand in a micelle microenvironment, a fast and sensitive flow injection CL method for PMS detection was proposed and applied to the analysis of different samples and PMS decomposition. Under the optimized conditions, a linear range was obtained from 4.0 × 10 –6 mol L –1 to 2.0 × 10 –4 mol L –1 with a high correlation coefficient ( r = 0.9997), detection limit of 5.0 × 10 –7 mol L –1 (S/ N = 3) and relative standard deviation of 2.4% for 1.0 × 10 –5 mol L –1 PMS ( n = 9). This was successfully applied to the determination of PMS in Virkon powder, tap water, and swimming pool water samples with satisfactory recoveries from 94.8% to 104.8% . In particular, the analytical frequency could be as fast as five samples per minute because there was no reaction step before analysis and the CL phenomenon was instantaneous. Therefore, this CL method has also been successfully applied to investigate the PMS decomposition profiles in carbon material (carbon nanotubes, carbon nanofibres, activated carbon and graphene oxide) catalysis systems, which followed pseudo‐first‐order kinetics with good correlation coefficients ( r > 0.9305). Quenching experiments and electron spin resonance spectra verified that the CL phenomenon was due to the formation of singlet oxygen, and that hydroxyl and sulfate radicals might be important in the generation of singlet oxygen. Tb(III) is the luminescent emitter according to the characteristics emission bands of the fluorescence and CL spectra in different media.